NUMERICAL MODELLING OF STEEL STRENGTHENING UNDERGROUND CYLINDRICAL TANK (Collection of scientific works «Modern structures of metal and wood», 2024)
Quite  often,  underground  tanks  designed  to  store  liquid  materials  lose  their operational suitability in a short period of operation in real conditions. The largest number of defects is  associated  with  the  loss  of  tank  shell  local  resistance.  It  was  carried  out  the  stress-strain  state analysis for a typical tank with a volume of 75.0 m 3  made of a cylindrical two-layer shell. There are determined  the  reasons  for  the  local  stability  loss  of  the  shells  and  the  corresponding recommendations are given. The purpose of the paper is to determine the tank’s stress-deformation state to identify the causes  of  deformations  of  the  casing  and  to  provide  appropriate  recommendations  for  its strengthening. It works in real operating conditions by the actual loading. The main load on the underground tank is the external pressure of the soil. The calculation of the tank is performed as for a horizontal cylindrical shell with elliptical sidewalls under the action of external pressure.